ANALISIS MODEL LEARNING CYCIE 7E DAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM MATA PELAJARAN AKUNTANSI DI SMK PERSADA HUSADA INDONESIA KOTA BEKASI - Alma Siwi Anggita; Ati Sumiati; Sri Zulaihati; Dwi Kismayanti Respati (JURNAL ILMIAH EDUNOMIKA, 2022)
The problem in this study is that there are differences in students' critical thinking skills between the Learning Cycle 7E and Problem Based Learning models. This study aims to determine the differences in students' critical thinking skills using the 7E Learning Cycle and Problem Based Learning models. This study uses a quantitative approach with experimental methods, and the data analysis techniques used are data analysis requirements testing and hypothesis testing. The results of this study conclude that the 7E Learning Cycle and Problem Based Learning models can improve the critical thinking skills of students majoring in accounting at SMK Persada Husada Indonesia Bekasi City. There is a significant difference between the 7E Learning Cycle model and the Problem Based Learning model in improving students' critical thinking skills at SMK Persada Husada Indonesia Bekasi City. Better results were obtained by the Learning Cycle 7E learning model compared to the Problem Based Learning learning model as evidenced by the average score of students on the posttest results. It was proven that the posttest results in Learning Cycle 7E were higher than Problem Based Learning. And the results of the study, for aspects of analyzing and concluding the two learning models were appropriate to use because respondents in the experimental class and control class did not find any errors during the posttest. Keywords : Learning Cycle 7E Model, Problem Based Learning, Critical Thinking Ability